1997
DOI: 10.1897/1551-5028(1997)016<1583:tccale>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Calux (Chemical-Activated Luciferase Expression) Assay Adapted and Validated for Measuring TCDD Equivalents in Blood Plasma

Abstract: A method was developed to isolate lipophilic compounds efficiently from small aliquots of blood plasma and test these for total dioxin-like toxic potency using recombinant rat (H4IIE) and mouse (Hepa1c1c7) hepatoma cell lines, containing the firefly (Photinus pyralis) luciferase gene under trans-activational control of the aryl hydrocarbon receptor (AhR). For this experiment, blood plasma was used originating from eider ducks (Somateria mollissima) that had been dosed with 3,3Ј,4,4Ј-tetrachlorobiphenyl (PCB-77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 28 publications
(47 reference statements)
1
27
0
1
Order By: Relevance
“…Furthermore, the rapidity of our analysis (which minimizes PAH metabolism) reveals that PAHs are more active than previously reported, suggesting that previous cell bioassay analyses may have underestimated the induction potency of PAHs. Other studies by our laboratory and collaborating investigators have shown that this bioassay method can also be used to evaluate Ah-active compounds present in a variety of different biological and nonbiological matrices, such as serum, sediment, and whole-product extracts [29,30,[33][34][35][36]. While such cell bioassay systems do not directly determine the toxicity of such AhR ligands, results can contribute to a more complete assessment of the potential biological and toxic effects of such exposure when combined with results using other methods, such as determination of acute toxicity, mutagenicity, and carcinogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the rapidity of our analysis (which minimizes PAH metabolism) reveals that PAHs are more active than previously reported, suggesting that previous cell bioassay analyses may have underestimated the induction potency of PAHs. Other studies by our laboratory and collaborating investigators have shown that this bioassay method can also be used to evaluate Ah-active compounds present in a variety of different biological and nonbiological matrices, such as serum, sediment, and whole-product extracts [29,30,[33][34][35][36]. While such cell bioassay systems do not directly determine the toxicity of such AhR ligands, results can contribute to a more complete assessment of the potential biological and toxic effects of such exposure when combined with results using other methods, such as determination of acute toxicity, mutagenicity, and carcinogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several recombinant cell bioassay systems using luciferase-based reporters have been developed for the detection and relative quantitation of AhR-active chemicals and compounds in a variety of different biological and nonbiological matrices. Although most systems have emphasized analysis of HAH congeners [20][21][22][23], several have evaluated induction resulting from PAH analysis [24][25][26]. The most commonly used bioassays rely on recombinant hepatoma cell lines that contain a stably transfected AhR-responsive luciferase gene.…”
Section: Introductionmentioning
confidence: 99%
“…the Dr calUX bioassay has shown a high agreement with congener-specific methods and has been used in many epidemiologic and biomonitoring studies. 14,34,37,43-49 the protocol for sample processing has been presented in further details previously, 44,50 and additional details are provided in the eappendix (http://links.lww.com/eDe/a754). the assay analysis was performed on 791 mother and 269 cord blood samples with enough fat to express the bioassay results per gram fat.…”
Section: Dr Calux Bioassaymentioning
confidence: 99%
“…This bioassay is a welldocumented assay for measuring dioxin-like compounds [8][9][10]. The CALUX (also called DR-LUC) assay makes use of an AhR-reporter gene system where dioxins and dioxin-like compounds bind to and activate AhR-mediated luciferase activity in a genetically modified rat liver cell line.…”
Section: Introductionmentioning
confidence: 99%